Pengaruh Motivasi Terhadap Kinerja Karyawan pada Kantor Unit Pelayanan Teknis Daerah Peureulak Aceh Timur - Yusraini; M Djamil (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2021)
This study aims to investigate the effect of motivation on employee performance at the Peureulak Regional Technical Service Unit Office, East Aceh. This study used a quantitative approach by collecting data through questionnaires which were distributed to 30 employee respondents. Data analysis was performed using multiple linear regression. The results showed that motivation has a significant positive effect on employee performance. There are several motivational factors that affect employee performance, namely appreciation, promotion, and work atmosphere. These findings can provide input for the management of the Peureulak Regional Technical Service Unit Office, East Aceh in increasing employee motivation and their performance. The scientific findings of this study indicate that motivation has a positive and significant influence on employee performance at the Peureulak Regional Technical Service Unit Office, East Aceh. More specifically, the factors of appreciation, promotion, and work atmosphere have a positive and significant influence on employee motivation and their performance. This shows that management needs to pay special attention to increasing employee motivation by providing appropriate awards and promotions, as well as creating a conducive working atmosphere. Thus, employees will feel valued and motivated to provide better performance, so as to increase office productivity and efficiency in providing technical services to the public. These findings can serve as a reference for management in increasing the motivation and performance of employees at the Peureulak Regional Technical Service Unit Office, East Aceh and other organizations